The intestinal microbiota: Towards a multifactorial integrative model. Eubiosis and dysbiosis in morbid physical and psychological conditions - Giulio Perrotta (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
The human intestinal microbiota is considered "an organ within an organ", partially shrouded in mystery, as the issue related to the bacterial component but less the viral component and the other microorganisms present has been thoroughly investigated. To date, research has focused attention on the bacterial component and on the correlations between intestinal dysbiosis and the onset or worsening of dozens of physical and psychological pathological conditions, as well as integrative therapies to re-establish eubiosis, linked to targeted prebiotics and probiotics; however, the scientific community has not yet focused on the exact distribution of all the microorganisms that are part of the microbiota and the complete mapping of the microbiome, as well as the development of a protocol of specific therapies to be implemented (integrative or with monoclonal antibodies) to facilitate the reconstructive processes of natural eubiosis. If therefore, knowing the Microbiome (and the Microbiota) is important from a neuroimmunological point of view, on the other hand, it is essential to deepen the correlations with the onset of some physical and psychological pathologies; in particular, focusing the studies on the already well-known "microbiota-intestine-brain" axis would help to demonstrate whether the onset of psychopathological conditions are a contributing cause of dysbiosis or (more likely) dysbiosis causes an altered production of serotonin, dopamine, GABA and noradrenaline, capable of generating or worsening directly related psychopathologies, such as anxiety, depression, mood disorders, schizophrenia, psychotic and personality disorders. On the other hand, it is known that psychiatric drug therapies do not cure the morbid condition but aim to stabilize the patient who becomes dependent on it, and then witness a rapid worsening in the event of drug suspension or interruption. If we then wanted to search for an objective to investigate, the writer proposes to focus on the hypothesis according to which intervening on intestinal dysbiosis could decrease or eliminate the neurobiochemical cause at the base of many psychic disorders, such as anxiety, depression, bipolar and psychotic disorders, decreasing or eliminating the necessarily prescribed drug therapy.